A grid-based reliable multi-hop routing protocol for energy-efficient wireless sensor networks. (March 2018) - Chen, Zhansheng; Shen, Hong
Due to the limited energy and the non-equivalence of wireless sensor network nodes, it is imperative to reduce and rationally use the energy consumption of the nodes to prolong the network lifetime. Clustering routing algorithm can address the problem efficiently. In this article, a grid-based reliable multi-hop routing approach for wireless sensor networks is proposed. In order to minimize and balance the energy consumption, our proposed protocol, grid-based reliable multi-hop routing protocol, optimizes the cluster head election process by combining individual ability which consists of node's residual energy and node's location, and local cognition which can balance energy consumption among clusters via a consultative mechanism based on cluster head's lifetime expectancy, while considering data forwarding delay and reliable transmission of data. Simulation results show that grid-based reliable multi-hop routing protocol has improved stability period as compared to other protocols. Meanwhile, grid-based reliable multi-hop routing protocol has better performance in energy efficiency, data forwarding delay, and reliable transmission of data.